Moving from infancy to young adulthood : a contemporary review of the development of the Virgin Islands - Lewis-Ambrose, Dana (Cambridge Scholars Publishing, 2013)
Moving from Infancy to Young Adulthood is a contemporary review of the development of the Virgin Islands (BVI) within an economic and political context. Specifically, this book is an excellent medium presenting contemporary perspectives of how the BVI has grown and evolved over the past 50-60 years. Whenever a country is seriously considering its development path over a period of time, it must engage in national development and nation building activities, which will allow its citizens to acc ...